Transanal Excision of Anorectal Tumors Using the Multifire EndogiaTM 30 - John J O’Connor (Canadian Journal of Gastroenterology)
Transanal excision of rectal tumours is a viable technique for the removal of benign lesions and early small carcinomas. This report describes a technique for their early removal with the Endo-GIA stapling device.